Diálogos formativos para práticas pedagógicas inclusivas na educação infantil - Silva, Amanda Fernandes da (2017)
In Brazil, there is a growing mobilization aiming at the expansion and guarantee of the right to Education. Many social movements and various segments of society struggle in defense of Inclusive Education. Faced with the new paradigm of universal education, there is a broad spectrum of challenges in conceiving education within an inclusive perspective. In this sense, the continued formation of teachers in context stands out as a possibility for the transformation of the educational scenario. The present study aimed to analyze the inclusive practices of children 's education from the spaces of dialogue teacher training in a school in the municipality of Nossa Senhora do Socorro / SE. This work was of a qualitative nature and adopted as a theoretical-methodological presupposition the collaborative-critical research-action. The research was organized in three non-linear moments, configuring the spirals of action-reflection, namely: knowing the educational practices of early childhood education; To provide spaces for dialogue-training of the subjects involved in inclusion and to evaluate changes in educational practices. The data produced were categorized and listed by thematic regularities of analysis. As a result of the research, it was observed that the school presents an unsatisfactory infrastructure for early childhood education and school organization as an obstacle to the achievement of collective moments of learning and professional training, it was also noted incipience in the work of school inclusion. Given this context, the pedagogical mediation of the child, case study and workshop of AAC/AT were prioritized as spaces for dialogue training. From real situations of the context reflected theoretically it is possible to visualize new possibilities in the pedagogical practices and organization of the school routine of the infantile education, in order to favor the participation of the student with the deficiency in the actions planned and developed by the school. Collaborative work in the daily life of children's education has proved to be potent in the process of professional teacher training and in the process of effecting school inclusion and child development.